Valley of the Shadow of Death -- Most Hallowed Ground 1864. - Ken Burns (Hollywood, CA PBS Home Video, 1990)
Hailed as a film masterpiece and landmark in historical storytelling, Ken Burn's epic documentary brings to life America's most destructive--and defining--conflict.
Keywords: Civil War -- documentary; Episodes Six and Seven